Inhibitor Antibody Development and T Cell Response to Human Factor VIII in Murine Hemophilia A - Qian, Jiahua; Borovok, Marina; Bi, Lei; Kazazian, Haig H., Jr.; Hoyer, Leon W. (Thrombosis and Haemostasis, 1999)
In order to understand better the mechanism of inhibitor formation in hemophilia A patients, we have characterized the immune response to human factor VIII in a murine model of hemophilia A. Mice with severe factor VIII deficiency caused by targeted gene disruptions in exons 16 and 17 were injected intravenously with human factor VIII. Anti-factor VIII was absent or was detected at only very low levels in hemophilic mice of both strains after a single injection of 0.2 μg factor VIII, but it was present in most mice after a second exposure. Subsequent exposures led to high titer anti-factor VIII antibodies in both ELISA and inhibitor assays. A human factor VIII-specific T cell proliferative response was detected with spleen cells obtained three days after a single injection with human factor VIII, before mice had detectable anti-factor VIII antibodies. Subsequent exposures to factor VIII were followed by an increased T cell proliferative response. These studies indicate that murine hemophilia A is a good model for the study of the immune response to human factor VIII, especially the role of the T cell in the early steps in inhibitor antibody formation.